2018
DOI: 10.1158/1078-0432.ccr-17-2219
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Cancer Stem-Like Cells Under Metabolic Stress via CaMK2α-mediated Upregulation of Sarco/Endoplasmic Reticulum Calcium ATPase Expression

Abstract: Cancer cells grow in an unfavorable metabolic milieu in the tumor microenvironment and are constantly exposed to metabolic stress such as chronic nutrient depletion. Cancer stem-like cells (CSC) are intrinsically resistant to metabolic stress, thereby surviving nutrient insufficiency and driving more malignant tumor progression. In this study, we aimed to demonstrate the potential mechanisms by which CSCs avoid Ca-dependent apoptosis during glucose deprivation. We investigated cell viability and apoptosis unde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Intracellular Ca 2+ level-dependent inhibition of mitochondrial motility occurs in response to spatial and temporal requirements and in order to enhance local Ca 2+ buffering. In a previous report, we showed that CSCs express sarco/endoplasmic reticulum Ca 2+ -ATPase to avoid apoptosis, which occurs after Ca 2+ overload under glucose deprived conditions [ 140 ]. How Ca 2+ -dependent mitochondrial movement in CSCs is accomplished is presently not well understood.…”
Section: Cytoskeletonmentioning
confidence: 99%
“…Intracellular Ca 2+ level-dependent inhibition of mitochondrial motility occurs in response to spatial and temporal requirements and in order to enhance local Ca 2+ buffering. In a previous report, we showed that CSCs express sarco/endoplasmic reticulum Ca 2+ -ATPase to avoid apoptosis, which occurs after Ca 2+ overload under glucose deprived conditions [ 140 ]. How Ca 2+ -dependent mitochondrial movement in CSCs is accomplished is presently not well understood.…”
Section: Cytoskeletonmentioning
confidence: 99%
“…Furthermore, the therapeutic potential of the dual inhibition of glycolysis and Ca 2+ signaling should be considered. In support of this, combined treatment with a SERCA inhibitor (thapsigargin) and the glycolytic inhibitor 2-deoxy-d-glucose has recently shown significant anti-tumor effects in preclinical studies (Park et al, 2018).…”
Section: Calcium -Glucose Metabolism Interplay Ca 2+ Regulation and Gmentioning
confidence: 88%
“…Thus, the dual pharmacological modulation of Ca 2+ signaling and metabolism might have synergistic anticancer effects. Interestingly, preclinical evidence for the therapeutic potential of combined strategies is emerging (Park et al, 2018), yet it remains to be determined whether dual targeting will be effective in humans.…”
Section: Introductionmentioning
confidence: 99%
“…RNA labeling and hybridization were performed using the Agilent One-Color Microarray-based Gene Expression Analysis protocol (Agilent Technologies, V 6.5, 2010). Additional protocol and data analysis details are described in our previous article [ 47 ].…”
Section: Methodsmentioning
confidence: 99%